Development of the Korean Facial Emotion Stimuli: Korea University Facial Expression Collection 2nd Edition - Kim, Sun-Min; Kwon, Ye-Jin; Jung, Soo-Yun; Kim, Min-Ji; Cho, Yang Seok; Kim, Hyun Taek; Nam, Ki-Chun; Kim, Hackjin; Choi, Kee-Hong; Choi, June-Seek (Frontiers in Psychology, 2017)
Background: Developing valid emotional facial stimuli for specific ethnicities creates ample opportunities to investigate both the nature of emotional facial information processing in general and clinical populations as well as the underlying mechanisms of facial emotion processing within and across cultures. Given that most entries in emotional facial stimuli databases were developed with western samples, and given that very few of the eastern emotional facial stimuli sets were based strictly on the Ekman’s Facial Action Coding System, developing valid emotional facial stimuli of eastern samples remains a high priority. Aims: To develop and examine the psychometric properties of six basic emotional facial stimuli recruiting professional Korean actors and actresses based on the Ekman’s Facial Action Coding System for the Korea University Facial Expression Collection-Second Edition (KUFEC-II). Method: Stimulus selection was done in two phases. First, researchers evaluated the clarity and intensity of each stimulus developed based on the Facial Action Coding System. Second, researchers selected a total of 399 stimuli from a total of 57 actors and actresses, which were then rated on accuracy, intensity, valence, and arousal by 75 independent raters. Conclusions: The hit rates between the targeted and rated expressions of the KUFEC-II were all above 80%, except for fear (50%) and disgust (63%). The KUFEC-II appears to be a valid emotional facial stimuli database, providing the largest set of emotional facial stimuli. The mean intensity score was 5.63 (out of 7), suggesting that the stimuli delivered the targeted emotions with great intensity. All positive expressions were rated as having a high positive valence, whereas all negative expressions were rated as having a high negative valence. The KUFEC II is expected to be widely used in various psychological studies on emotional facial expression. KUFEC-II stimuli can be obtained through contacting the corresponding authors.